Adaptive Peacebuilding Programming Through Effective Feedback Loops: Promising Practices - Barnard-Webster, Kiely; Jean, Isabella (CDA, 2018)
This case study report was developed by CDA’s part of Peacebuilding Evaluation Consortium collaborative research on the use of feedback loops in support of adaptive programming. Feedback loops are just one element of adaptive programming and are defined and used in different ways by organizations working on social change, peace and development issues. This document includes key findings from our desk review of reports and grey literature, key informant interviews, observations documented during CDA’s advisory and learning engagements with peacebuilding partners as well as the case study on SFCG’s feedback processes in Burundi. The findings are most relevant to program and M&E staff but have implications for senior management and policymakers in light of growing interest in strengthening adaptive management.

Peacebuilding design, monitoring, and evaluation: A Training Package for participants and trainers at intermediate to advanced levels - Ernstorfer, Anita; Barnard-Webster, Kiely (Carnegie Corporation, 2019)
This training package includes 7 Training Modules and a set of Annexes (Annexes A-O). The Training Modules build on each other and should ideally be used in a sequenced way in a training setting. However, for groups with specific training needs around particular areas, modules can also be used individually, but need to be tailored by the trainers and facilitators to meet the needs of specific audiences. The annexes provide worksheets and hand-outs that can be used as resources during the training for specific modules and exercises.